Inducing enantioselective crystallization with and self‐assembly of star‐shaped hybrid polymers prepared via "grafting to" strategy. Issue 1 (8th November 2021) - Zou, Hui; Liang, Wen‐Quan; Wu, Qi‐Liang; Zhou, Li; Hou, Xiao‐Hua; Liu, Na; Wu, Zong‐Quan
Abstract: Helical polymers present some interesting and distinctive properties, and one of the most distinguished applications of them is the chiral recognition and resolution of enantiomers. In this work, star‐shaped hybrid helical poly (phenyl isocyanide) (PPI) with polyhedral oligomeric silsesquioxanes (POSS) as the core was designed and synthesized by "grafting to" strategy. The homoarm star‐shaped hybrid POSS‐(PPI)8 was first obtained by the click reaction between azide‐modified POSS (POSS‐(N3 )8 ) and alkynyl‐modified PPI (PPI‐Alkynyl). The hybrid POSS‐(PPI)8 was with predominated left‐handed helical conformation and exhibited excellent ability in the enantioselective crystallization of racemic compounds. In the meantime, heteroarm star‐shaped hybrid (PEG)4 ‐POSS‐(PPI)4 was prepared by the click reaction of POSS‐(N3 )8 with PPI‐Alkynyl and alkynyl‐modified poly (ethylene glycol) (PEG‐Alkynyl). The hybrid (PEG)4 ‐POSS‐(PPI)4 was amphiphilic, and it could self‐assemble to form spherical micelles in aqueous solutions. Abstract : Well‐defined star‐shaped hybrid helical poly (phenyl isocyanide)s with POSS core were designed and synthesized by "grafting to" strategy. The enantioselective crystallization ability, as well as the self‐assembly behavior of the star‐shaped hybrid polymers, was investigated.